Ser7 Phosphorylation of the CTD Recruits the RPAP2 Ser5 Phosphatase to snRNA Genes - Sylvain Egloff; Justyna Zaborowska; Clélia Laitem; Tamás Kiss; Shona Murphy (2011)
The carboxy-terminal domain (CTD) of the large subunit of RNA polymerase II (Pol II) comprises multiple heptapeptide repeats of the consensus Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7. Reversible phosphorylation of Ser2, Ser5, and Ser7 during the transcription cycle mediates the sequential recruitment of transcription/RNA processing factors. Phosphorylation of Ser7 is required for recruitment of the gene type-specific Integrator complex to the Pol II-transcribed small nuclear (sn)RNA genes. Here, we show that RNA Pol II-associated protein 2 (RPAP2) specifically recognizes the phospho-Ser7 mark on the Pol II CTD and also interacts with Integrator subunits. siRNA-mediated knockdown of RPAP2 and mutation of Ser7 to alanine cause similar defects in snRNA gene expression. In addition, we show that RPAP2 is a CTD Ser5 phosphatase. Taken together, our results indicate that during transcription of snRNA genes, Ser7 phosphorylation facilitates recruitment of RPAP2, which in turn both recruits Integrator and dephosphorylates Ser5.